2013
DOI: 10.1123/ijsnem.23.4.369
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effects of L-arginine on Hormonal and Metabolic Responses During Submaximal Exercise in Trained Cyclists

Abstract: L-arginine may enhance endurance performance mediated by two primary mechanisms including enhanced secretion of endogenous growth hormone (GH) and as a precursor of nitric oxide (NO); however, research in trained participants has been equivocal. The purpose was to investigate the effect of acute L-arginine ingestion on the hormonal and metabolic response during submaximal exercise in trained cyclists. Fifteen aerobically trained men (age: 28 ± 5 y; body mass: 77.4 ± 9.5 kg; height: 180.9 ± 7.9 cm; VO2max: 59.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 54 publications
3
21
0
2
Order By: Relevance
“…Furthermore our data does not support the auto-negative feedback loop via enhanced IGF-1 or GH since IGF-1 was not elevated from rest and GH did not rise before the exercise bout nor was there any significant difference between conditions. In addition, previous research found no effect of L-arginine supplementation on insulin at rest or plasma glucose and carbohydrate oxidation during aerobic exercise (Forbes et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore our data does not support the auto-negative feedback loop via enhanced IGF-1 or GH since IGF-1 was not elevated from rest and GH did not rise before the exercise bout nor was there any significant difference between conditions. In addition, previous research found no effect of L-arginine supplementation on insulin at rest or plasma glucose and carbohydrate oxidation during aerobic exercise (Forbes et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…The AAKG supplement group increased plasma L -arginine levels, but there was no difference found in NO x levels between groups. A study conducted by Forbes et al [ 161 ] assessing the effects of L -arginine supplementation among trained cyclists was mentioned previously in the growth hormone section. This study also concluded that L -arginine supplementation did not have any infl uence on NO x levels.…”
Section: Nitric Oxide-boosting Supplementsmentioning
confidence: 99%
“…Another L -arginine study evaluated supplementation among trained cyclists [ 161 ]. Fifteen males were assigned to either a placebo or L -ARGININE supplement (0.075 g/kg body mass) before a submaximal exercise.…”
Section: Human Growth Hormonementioning
confidence: 99%
“…Одной из таких фармакологически перспектив-ных субстанций в последние годы стал L-аргинин, обладающим многогранным физиологическим дей-ствием на организм в условиях напряженной мы-шечной деятельности [25,33,34,40]. Аргинин яв-ляется незаменимой для синтеза белка в мышцах аминокислотой; прекурсором креатина, что потен-циально подразумевает наличие анаболических свойств в мышечной ткани; модулятором образо-вания эндогенного гормона роста с последующим косвенным стимулированием анаболических про-цессов; оказывает непрямое стимулирующее дей-ствие на синтез оксида азота, играет существен-ную роль в обмене адениловых нуклеотидов, что сопровождается расширением кровеносных сосу-дов, включая сосуды скелетных мышц и миокарда со снижением потребности в кислороде, ускорени-ем восстановления и замедлением развития утом-ления; является мощным кардиопротекторным средством [24,37,42,48,54].…”
unclassified
“…имеют недостаточно высо-кий уровень доказательности [23]. Кроме того, аб-солютное большинство работ относительно влия-ния L-аргинина на работоспособность проведены или при разовом/курсовом применением пищевых добавок (а не лекарственных препаратов) у спорт-сменов, или в эксперименте [25,34,41,55,57].…”
unclassified